2017
DOI: 10.1111/jgh.13712
|View full text |Cite
|
Sign up to set email alerts
|

East Asian perspective on the interaction between proton pump inhibitors and clopidogrel

Abstract: Both proton pump inhibitors (PPIs) and clopidogrel are widely prescribed in the Asia-Pacific population. PPIs are the mainstay therapeutic agents for prophylaxis against aspirin gastropathy and for acid-related disorders including gastroesophageal reflux disease. They are also co-prescribed with oral anticoagulant agents and with dual-antiplatelet therapy for the treatment and prevention of gastrointestinal bleeding. Clopidogrel belongs to the drug class of thienopyridines and is currently the most widely pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
(140 reference statements)
0
4
1
1
Order By: Relevance
“…15 Besides, similar increases in prescription rates have also been observed in many other countries. [16][17][18][19] Although our result revealed Open access that the prevalence of PPI use was less than that of other reports, an appreciable increase in PPI utilisation has been witnessed in other regions in China 20 which could be reflected in a study conducted, in particular, for injectable PPIs. 4 These facts pose serious queries and concerns on the inappropriate use of PPIs, the occurrence of potential side effects and the increase in healthcare costs.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…15 Besides, similar increases in prescription rates have also been observed in many other countries. [16][17][18][19] Although our result revealed Open access that the prevalence of PPI use was less than that of other reports, an appreciable increase in PPI utilisation has been witnessed in other regions in China 20 which could be reflected in a study conducted, in particular, for injectable PPIs. 4 These facts pose serious queries and concerns on the inappropriate use of PPIs, the occurrence of potential side effects and the increase in healthcare costs.…”
Section: Discussioncontrasting
confidence: 85%
“…In March 2010, The Food and Drug Administration (FDA) issued a 'black box warning' to warn that the prescription on clopidogrel should avoid concomitant use of omeprazole or esomeprazole if the patients have been identified as CYP2C19 poor metabolisers, 33 especially in East-Asian patients for whom the CYP2C19 loss-of-function (LoF) allele is associated with an increased risk of adverse cardiovascular outcomes when treated with clopidogrel. 19 In this case, lansoprazole and pantoprazole could be considered as a rational choice. 34 In terms of cost-effective prescribing, the DDC results showed that the highest average daily costs of PPIs were injectable omeprazole, followed by oral esomeprazole.…”
Section: Open Accessmentioning
confidence: 99%
“…23 Concomitantly administered pantoprazole or rabeprazole did not affect the pharmacokinetic and antiplatelet efficacy of clopidogrel because of the weaker affinity for the CYP2C19 isoenzyme. 24,25 Moreover, recent studies 26,27 in East Asian cohorts suggests that the potential of PPIs to attenuate the efficacy of clopidogrel could be minimized by the use of newer PPIs with weaker affinity for the CYP2C19 isoenzyme, namely, pantoprazole, dexlansoprazole, and rabeprazole. In our study, pantoprazole and lansoprazole were the two most commonly prescribed PPIs for acute UGIB.…”
Section: Discussionmentioning
confidence: 99%
“…As PPI use increases worldwide, growing concerns about PPI complications have been raised [ 6 , 7 , 8 ]. Specifically, drug interaction with clopidogrel, which is an antiplatelet agent classified as thienopyridines, has been postulated in many recent studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Both PPIs and clopidogrel are metabolized by hepatic cytochrome P450 (CYP) enzymes; in the presence of CYP2C19 inhibition, PPIs could reduce the efficacy of clopidogrel’s protective roles in cardiovascular events [ 22 ].…”
Section: Introductionmentioning
confidence: 99%